MOBILE MONEY SERVICES: A LIQUIDITY THREAT TO UGANDA’s COMMERCIAL BANKS - Kamukama, Nixon; Tumwine, Sulait (African Journal of Accounting, Economics, Finance and Banking Research., 2012)
The purpose of this paper istwofold: (i) to establish whether the growth in mobile commerce in Uganda has disadvantaged commercial banks in way that their liquidity has been indirectly stolen(Pickens, 2009) and (ii)to examine the extent to which Mobile Money services have affected liquidity position of Uganda’s commercial banks. The paper used a cross sectional study design and emphasis was put on quantitative research approach. However, for data analysis, descriptive statistics together with linear regression tests were applied. Findings indicated that Ugandan commercial banks are in liquidity crisis, a phenomena that has constrained their lending capacity. What is more unfortunate is that the commercial banks’ liquidity ratios are falling short of the Bankof Uganda’s thresholdratio of 20% representing a ratio of total liquid assets to total deposit liability. Single-handedly, mobile money services account for 36.7% of liquidity variance in Ugandan Commercial Banks. The study recommends that commercial banks should partner or enter into joint venture with mobile money operators. With such partnership, banks will have effective models to expand their physical reach into poor and rural areas. This arrangement will deliver the required level of proximity and low transaction costs, which are essential in increasing client deposits, a source of liquidity. More so, commercial banks should take advantage of the products that are not provided by mobile operators. For example, credit or loan facilities and insurance services where banks have competitive advantage over mobile operators should be conveniently provided at a low cost to clients. It is hoped that this will build a strong bond between the client and the bank which guarantees regular flow of cash in or cash out transaction.
MOBILE MONEY SERVICES.
Keywords: Mobile Money services and Bank Liquidity.